Shari’ah and ethical issues in the practice of modified wakalah model in family takaful - Htay, Sheila Nu Nu; Syed, Ahmed Salman (Center for Promoting Ideas (CPI), 2013)
Takaful has been acknowledged as insurance which is in line with Shari’ah principles. Due to the prohibited elements such as interest, uncertainty and gambling in the insurance practices, Takaful has been introduced by the Muslim scholars. Takaful is one of the fast growing industries in Islamic finance and it widely spreads into both Muslim and non-Muslim countries. The rapid growth of the industry does not mean that it is free from undesirable issues related to the Shari’ah and ethics. Therefore, the purpose of this paper is to highlight the Shari’ah and ethical issues in the practice of modified Wakalah model in family Takaful. This paper focuses on the issues arisen from the concept of Tabaru’, surplus distribution and agency problem. These issues might be the mismatch of the original concept of Islamic principles and the current needs of the contracts. This paper does not intent to provide the solution for the issues and hence, future research should focus on it.